Admisje notarialne w diecezji płockiej u schyłku średniowiecza /Admissions of Notaries Public in the Diocese of Płock in the Late Middle Ages/ - Kobylińska, Ewa (Studia Geohistorica, 2017)
Atlas Fontium The article presents the ways of granting 73 notarial admissions by the bishops and officials of Płock in the years 1448–1525 and the practice of registering this fact in their offices. It also deals with the creation of notaries and Comes and Vice-Comes persons mentioned in the admissions. Besides, it discusses the admitted notaries public – their social and territorial background, university education, family relations and the course of their career. The conducted studies show that the greatest role among the admitted was played by the Mazovian gentry, first of all in the western part of the Płock diocese and the central part of the Warsaw archdiaconate. The education of notaries public admitted in Płock was comparable to that represented by notaries from other dioceses. They obtained church beneficies in Mazovia relatively often. There, they were active as the clergy of the chapter and the parishes, as well as notaries or teachers. In particular, the present article emphasizes the role of social relations in notarial admission and their effect on further career. The text is complemented with the data base including all discovered information concerning the people who gained the right to perform notarial functions in the Płock diocese and a reproduction of admission entries, which in the majority of cases make it possible to find out the type duct of particular notaries public.